Kasetsartra Pinkaew (Lepidoptera: Tortricidae: Olethreutinae), a new genus from Thailand with the description of its type species - Pinkaew, Nantasak (Zootaxa, 2018)
Kasetsartra, gen. nov., is described from Thailand based on the type species, Kasetsartra fasciaura, sp. nov. Kasetsartra is characterized by a unique wing pattern, a conspicuous uncus in the male genitalia, and a dorsally expanded corpus bursae in the female genitalia. Adults, wing venation, and genitalia are illustrated, and their structure suggests a position in the tribe Enarmoniini.